2013
DOI: 10.1002/cbic.201300115
|View full text |Cite
|
Sign up to set email alerts
|

A Prototypical Small‐Molecule Modulator Uncouples Mitochondria in Response to Endogenous Hydrogen Peroxide Production

Abstract: A high membrane potential across the mitochondrial inner membrane leads to the production of the reactive oxygen species (ROS) implicated in aging and age-related diseases. A prototypical drug for the correction of this type of mitochondrial dysfunction is presented. MitoDNP-SUM accumulates in mitochondria in response to the membrane potential due to its mitochondria-targeting alkyltriphenylphosphonium (TPP) cation and is uncaged by endogenous hydrogen peroxide to release the mitochondrial uncoupler, 2,4-dinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…8E, a decrease in uorescence intensity was observed, which could be attributed to the H 2 O 2 existing in the tumor cells. 51 Consequently, all the results demonstrated that the multianalyte CDs sensing system has good potential for the imaging of intracellular H 2 O 2 .…”
Section: Intracellular Imaging Of Fe(iii) and H 2 Omentioning
confidence: 81%
“…8E, a decrease in uorescence intensity was observed, which could be attributed to the H 2 O 2 existing in the tumor cells. 51 Consequently, all the results demonstrated that the multianalyte CDs sensing system has good potential for the imaging of intracellular H 2 O 2 .…”
Section: Intracellular Imaging Of Fe(iii) and H 2 Omentioning
confidence: 81%
“…For uncouplers to work safely, these compounds should cause uncoupling that increases very little as their concentration rises, potentially widening the difference between therapeutic and toxic doses and giving a wide therapeutic window (62). Recently, however, targeted uncoupling showing precise spatial and temporal control of mitochondrial function have been demonstrated, leading to the selective uncoupling of either individual or small groups of them within a cell (63,64). Such technology, if adapted to SR4 in the future, will increase its safety and potentially lower the effective maximum dose required for its cytotoxic effects on tumors.…”
Section: Discussionmentioning
confidence: 99%
“…442 The compound was shown to release “free” DNP in mitochondria under the conditions of H 2 O 2 production. A similar strategy was also proposed for mitochondria-targeted “caged” DNP, activatable by light (MitoPhotoDNP, Chart 64).…”
Section: Mitochondria-targeted Bioactive Compounds As Potential Thmentioning
confidence: 99%